Effect of Clay on Degradation of Poly(ethylene terephthalate)/Montmorillonite Nanocomposites - Habibi, Sima; Rashidi, Abousaeed; Shahvaziyan, Mohammad; Bazgir, Saeed (Asian Journal of Chemistry, 2010)
Poly(ethylene terephthalate)/montmorillonite nanocomposites, with different contents of montmorillonite (1, 3 and 5 wt %), were prepared via melt compounding. The dilute solution viscosity technique was used to evaluate the intrinsic viscosity of poly(ethylene terephthalate)/ montmorillonite nanocomposites. The incorporation of clay reduces the intrinsic viscosity of polymer matrix. Their thermal stability were investigated by using thermogravimetric analysis. Their nano-dispersion morphology were confirmed by X-ray diffraction and transmission electron microscopy.